A Study on the Impact of Financial Inclusion for Inclusive Development (Journal of Advances and Scholarly Researches in Allied Education, 2023)
India has a long history of working towards financial inclusion. The term financial inclusionrefers to the practise of guaranteeing low-income individuals quick and low-cost access to financialservices and credit delivery. Assuring low-income individuals can easily access, use, and benefit from theformal financial system is central to Financial Inclusion's mission to foster economic expansion.Examining elements is crucial for achieving the goal of financial inclusion and, ultimately, for fosteringrobust economic development that results in equitable growth.